1992
DOI: 10.1111/j.1443-1661.1992.tb00091.x
|View full text |Cite
|
Sign up to set email alerts
|

Injection Sclerotherapy for Esophageal Varices after Total Gastrectomy: Case Reports of Two Patients

Abstract: Injection sclerotherapy was performed in two patients with esophageal varices who had undergone a total gastrectomy and Roux‐en‐ Y esophagojejunostomy for gastric cancer. Both of the patients were diagnosed as having postnecrotic liver cirrhosis due to serum hepatitis. The first patient developed esophageal varices after surgery. The second patient had recurrent esophageal varices after surgery for both gastric cancer and the esophageal varices. Five percent ethanolamine oleate was the sclerosant used together… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Endoscopic injection sclerotherapy (EIS) in conjunction with varicography is the most effective means for treating esophageal varices [3]. Up to now, we have seen two cases of esophageal varices after total gastrectomy treated with EIS [2], but this method is difficult when the varices are small, as in the present case.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Endoscopic injection sclerotherapy (EIS) in conjunction with varicography is the most effective means for treating esophageal varices [3]. Up to now, we have seen two cases of esophageal varices after total gastrectomy treated with EIS [2], but this method is difficult when the varices are small, as in the present case.…”
Section: Discussionmentioning
confidence: 86%
“…Esophagojejunal varices after total gastrectomy are supplied by branches of the jejunal vein of the arcade of the ascending jejunal limb [2]. In the present case, the blood flow measurement with the Doppler flow velocity guidewire indicated that the blood flow reversed at the turning point of the ascending jejunal vein (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…Three-dimensional CT, including MIP images, is a noninvasive imaging method, and these images allow for easy recognition of the hemodynamics and vascular anatomy. Several promising treatments for esophagojejunal varices, including surgical and endoscopic procedures, have been reported, but there have been few reports presenting a successful treatment for esophagojejunal varices after gastrectomy [11][12][13][14]. Surgical and endoscopic approaches are occasionally unsuccessful because of severe liver dysfunction and an intricate configuration of the alimentary tract after surgery, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, we decided to use the EIS procedure more than once until we achieved obliteration of the afferent jejunal varices. There has been only one English case report in the medical literature demonstrating the successful management of esophagojejunal varices with EIS using EOI [13].…”
Section: Discussionmentioning
confidence: 98%
“…Esophagojejunal varices arising after total gastrectomy and esophagojejunostomy are a rare complication of portal hypertension [1][2][3]. Endoscopic treatments can become challenging due to fibrosis and bleeding on the jejunal side after anastomosis.…”
mentioning
confidence: 99%